Pubertal development in adolescents with menstrual disorders - Alberto Roteta Dorado; Pilar Almaguer Sabina; Hussimy Marchena Morera; Maidelin Conde Cueto; Mónica González Brito (Medisur)
Introduction: Abnormal uterine bleeding is the presence of an excessive and prolonged menstrual bleeding over several consecutive cycles. It is one of the first complaints in pediatric gynecology and is the most common cause dysfunctional uterine bleeding. Objective: To characterize adolescents with menstrual disorders attending gynecology clinic in child and adolescent onset of puberty. Method: A descriptive, longitudinal and prospective. Universe: 88 adolescents seen at the gynecology children and youth in the province of Cienfuegos with menstrual disorders in 2008. Sample: 64 patients with rhythm disturbances of the menstrual cycle and excessive bleeding. Procedure: During the first consultation was found in the following medical records: age, onset of puberty, age at menarche, breast development and pubic hair development. The data were processed by SPSS program and expressed as numbers and percentages. Results: 43.8% of the adolescents studied were between 14 and 16 years, 29.7% began puberty at age 9, 31.3% had their menarche at age 11, 46, 87% were in Tanner stage IV of breast development and 56.25% in Tanner stage IV for pubic hair. Conclusion: There were no alterations in pubertal development in adolescents with menstrual disorders studied.